Periodontal therapy and glycaemic control among individuals with type 2 diabetes: reflections from the PerioCardio study. Issue 4 (1st June 2016) - Kapellas, K; Mejia, G; Bartold, PM; Skilton, MR; Maple‐Brown, LJ; Slade, GD; O'Dea, K; Brown, A; Celermajer, DS; Jamieson, LM
Abstract: Objectives: Diabetes mellitus and periodontal disease are highly prevalent among Indigenous Australian adults. Untreated periodontitis impacts glycaemic control in people with diabetes. The aim of this study was to report on the effect of periodontal therapy on glycaemic control among people with obesity. Methods: This subgroup analysis is limited to 62 participants with diabetes from the original 273 Aboriginal Australian adults enrolled into the PerioCardio study. Intervention participants received full‐mouth non‐surgical periodontal scaling during a single, untimed session while controls were untreated. Endpoints of interest included change in glycated haemoglobin (HbA1c), C‐reactive protein (CRP) and periodontal status at 3 months post‐intervention. Results: There were more females randomized to the treatment group ( n = 17) than control ( n = 10) while the control group had a higher overall body mass index (BMI) [mean (SD)] 33.1 (9.7 kg m −2 ) versus 29.9 (6.0 kg m −2 ). A greater proportion of males were followed up at 3 months compared to females, P = 0.05. Periodontal therapy did not significantly reduce HbA1c:ancova difference in means 0.22 mmol mol −1 (95% CI −6.25 to 6.69), CRP:ancova difference in means 0.64 (95% CI −1.08, 2.37) or periodontal status at 3 months. Conclusions: Non‐surgical periodontal therapy did not significantly reduce glycated haemoglobin in participants with type 2 diabetes. Reasons are likely to be multifactorial and may be influenced by persistent periodontal inflammation at the follow‐up appointments. Alternatively, the BMI of study participants may impact glycaemic control via alternative mechanisms involving the interplay between inflammation and adiposity meaning HbA1c may not be amenable to periodontal therapy in these individuals.